Answer:
t = (p - 1/2)/3
Step-by-step explanation:
p = 4t + 1/2 - t
combine like terms:
p = 3t + 1/2
subtract 1/2 from each side of the equation:
3t = p - 1/2
divide both sides by 3:
t = (p - 1/2)/3
Answer:
for 1 in the right side, corresponding is 3, for 2, you get 4, for 6, you get 8, and for 7, you get 9. pls follow and mark as brainliest
Step-by-step explanation:
So there is a rule
(+)(+)=+
(-)(+)= -
(+)(-)= -
So now if you subtract 6 with 7 you will end up having -1 as you’re answer. Hope this helps
Answer:
C) 4/(x+y)²
Step-by-step explanation:
start by expanding so it is written as 2÷(x+y)/(x+y)÷2.
Then rearrange so that it is 2×2/(x+y)×(x+y) or 4/(x+y)²
(2x^3)*(5x^2)+(2x^3)*(4)+(1)*(5x^2)+(1)*(4)
10x^5+8x^3+5x^2+4